ECONOMIC AND FINANCIAL IMPACT OF THE COVID-19 PANDEMIC ON BEAUTY CENTERS IN CIUDAD DEL ESTE - Yannet Flecha Escobar, Liz (Revista Gênero e Interdisciplinaridade, 2023)
The general objective of this research is to analyze the economic and financial impact of the Covid-19 Pandemic on beauty centers located in Ciudad Del Este. For this, the specific objectives dictated below are the following: to identify the services most affected by the outbreak of the Covid 19 pandemic, to describe the extent to which the decrease in services during the pandemic affects the profitability of beauty centers , and explain the marketing strategy that shopping centers should carry out to appease the level of debt due to the low liquidity flow caused by the decrease in services. This research is descriptive in nature; The hypothesis of said investigation is; the greater the impact, whether positive or negative, during the pandemic, the better or worse the situation will be in terms of economics and finances in beauty center companies.